2019
DOI: 10.4081/mi.2018.7913
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, work motivation, burn-out and stress perceptions benefits of a stress management program by autogenic training for emergency room staff: A pilot study

Abstract: Emergency room have particularly stressful work situations. Emergency room personnel cope with stressors on a daily basis. These stressors can be risks factor for burn out and for reduced quality of life and work motivation. Emergency room staff of one of ASP 3 CT urban hospital in Acireale, Italy participated to stress management program by autogenic training twice a month for 16 weeks. This program were prepared based on existing research and studies, and were conducted by clinical psychologists. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Relaxation techniques showed efficacy in managing stress, preventing burnout, and increasing work motivation, in particular autogenic training[ 62 ]. Relaxation techniques during COVID-19 confirmed their effectiveness as procedures apt to improve quality of life, work motivation, burnout and stress perceptions within the emergency department team[ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relaxation techniques showed efficacy in managing stress, preventing burnout, and increasing work motivation, in particular autogenic training[ 62 ]. Relaxation techniques during COVID-19 confirmed their effectiveness as procedures apt to improve quality of life, work motivation, burnout and stress perceptions within the emergency department team[ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of resilience interventions based on practicing autogenic training represents another supportive resource. Members of hospital emergency department teams reported a better quality of life, less stress perception, and decreased vulnerability to burn-out after participation in an autogenic training stress management program (Caponnetto et al, 2019). These kinds of interventions have also been found to be effective when delivered online.…”
Section: Discussionmentioning
confidence: 99%
“…Van Horne et al 53 reported a reduction in burnout for participants who attended three or more OASIS sessions versus those who reported not attending any sessions, however, this study did not report all mean scores. Dobie et al 55 and Duarte and Pinto-Gouveia 60 documented significantly reduced stress levels in participants following the intervention as measured by the DASS-21 and Caponnetto et al 59 also reported a significant reduction in perceived stress as measured by the PSS. It is worth noting however, that the study by Dobie et al 55 had strong limitations in that they recruited the smallest sample size of just nine participants.…”
Section: Table 1 Continuedmentioning
confidence: 96%
“…It is thought that the CPI may be more sensitive for measuring CS and therefore able to discern more subtle differences. 52 Individually focused interventions Thirty 1 4 7 12 17 37-51 53-55 [57][58][59][60][61][62][63] studies in this review implemented secondary level well-being interventions that targeted individual behavioural changes by aiming to minimise the effects of stress in participants through such techniques as relaxation training or promoting a positive mindset.…”
Section: Organisationally Focused Interventionsmentioning
confidence: 99%